2005
DOI: 10.1111/j.1365-2818.2005.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereological measures of trabecular bone structure: comparison of 3D micro computed tomography with 2D histological sections in human proximal tibial bone biopsies

Abstract: SummaryStereology applied on histological sections is the 'gold standard' for obtaining quantitative information on cancellous bone structure. Recent advances in micro computed tomography ( µ CT) have made it possible to acquire three-dimensional (3D) data non-destructively. However, before the 3D methods can be used as a substitute for the current 'gold standard' they have to be verified against the existing standard. The aim of this study was to compare bone structural measures obtained from 3D µ CT data set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(115 citation statements)
references
References 52 publications
2
111
2
Order By: Relevance
“…Various methods for filtering and measuring image features have been described before [21,[23][24][25][26][27][28][29][30][31][32]. Similar image features are current in studies on osteoporosis and bone structure [33][34][35][36][37][38][39].…”
Section: Image Processingmentioning
confidence: 99%
“…Various methods for filtering and measuring image features have been described before [21,[23][24][25][26][27][28][29][30][31][32]. Similar image features are current in studies on osteoporosis and bone structure [33][34][35][36][37][38][39].…”
Section: Image Processingmentioning
confidence: 99%
“…Many studies have been published on the accuracy of µCT measurements the relationship of instrument settings to the rendering of tooth morphology and the results of bone morphometry (Kim, Paik & Lee, 2005;Kohler et al, 2005;Olejniczak & Grine, 2006;Thomsen et al, 2005;Waarsing, Day & Weinans, 2004;Yeni et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These data highly threaten the internal validity and hence the external validity and generalizability of histomorphometric data in general. Nonetheless, it has been shown that correlation of the bone structural measurements between µCT and histomorphometry is very good, and even excellent when estimating bone volume to tissue volume (Müller et al 1998;Chappard et al 2005;Thomsen et al 2005). The latter was the primary outcome measurement in Paper 3.…”
Section: Histomorphometry and Its Correlation With 3d Imagingmentioning
confidence: 99%